Typical chest pain and precordial leads ST-elevation in patients with pacemakers – are we always looking at an acute myocardial infarction? - Ostojić, Marina M; Potpara, Tatjana S; Polovina, Marija M; Ostojić, Mladen M; Ostojić, Miodrag C (Vojnosanitetski pregled, 2015)
Introduction. Electrocardiographic (ECG) diagnosis of acute myocardial infarction (AMI) in patients with paced rhythm is difficult. Sgarbossa’s criteria represent helpful diagnostic ECG tool. Case report. A 57-year-old female patient with paroxysmal atrial fibrillation and a permanent pacemaker presented in the Emergency Department with prolonged typical chest pain and ECG recording suggestive for AMI. Documented ECG changes correspond to the first Sgarbossa’s criterion for AMI in patients with dual pacemakers (ST-segment elevation of ≥ 5 mm in the presence of the negative QRS complex). The patient was sent to catheterization lab where coronary angiogram reveled normal findings. ECG changes occurred due to pericardial reaction following two interventions: pacemaker implantation a month before and radiofrequency catheter ablation of AV junction two weeks before presentation in Emergency Department. Conclusion. This case report points out to the limitations of proposed criteria that aid in the recognition of AMI in patients with underlying paced rhythm and possible cause(s) of transient electrocardiographic abnormalities